Emodin Attenuates Lipopolysaccharide-Induced Acute Liver Injury via Inhibiting the TLR4 Signaling Pathway in vitro and in vivo - Ding, Yan; Liu, Pan; Chen, Zhi-Lin; Zhang, Shao-Jun; Wang, You-Qin; Cai, Xin; Luo, Lei; Zhou, Xuan; Zhao, Lei (Frontiers in Pharmacology, 2018)
Aims: In this study, we investigated the anti-inflammatory effects and possible molecular mechanisms of Emodin on lipopolysaccharide-induced acute liver injury through the toll-like receptor 4 (TLR4) signaling pathway in vitro and in vivo. Methods: Cell and animal models were established by lipopolysaccharide (LPS) and treated by Emodin. The TLR4 was overexpressed by lentivirus, and down-regulated by small interfering RNA (siRNA) technology. The mRNA and protein expression of TLR4 and downstream molecules were detected. The IL-6 and TNF-α levels in supernatant and serum were determined by ELISA. Immunofluorescence (IF) was used to label the areas of CD206 and ARG1 positive cells stained. Mice liver function and histopathological observations in hepatic tissue were assessed using biochemical tests and HE staining. Results: Administration of Emodin lessened the levels of TLR4 and its downstream molecules following LPS challenge. The inhibitory effect of Emodin was also confirmed in RAW264.7 cells in which TLR4 was overexpressed or knockdowned. Emodin suppressed expression of tumor necrosis factor-α (TNF-α) and interleukin(IL)-6. Additionally, Emodin also exerted significantly effect on the histopathological manifestation of LPS-induced acute liver injury, CD206 and ARG1 staining in liver tissues, and liver function. Conclusions: Emodin showed excellent hepatoprotective effects against LPS-induced acute liver injury possibly by inhibiting TLR4 signaling pathways.